Research on Surface Mounting Technology of Micromechanical Silicon Resonant Accelerometer - Libin Huang; Yang Gao (Institute of Advanced Engineering and Science, 2013)
Surface mounting technology is a key process in MEMS packaging. The finite element model of package structures was established in this paper according to the designed micromechanical silicon resonant accelerometer. The effects of package substrate materials, adhesive material characteristics, uneven adhesive thickness, and adhesive defects on the micromechanical silicon resonant accelerometer were analyzed with ANSYS software. Results showed that the package substrate material strongly affected the resonance frequency of the resonator after the application of surface mounting technology. The Young’s modulus and thermal expansion coefficient of adhesives were found to be important factors that affect chip thermal stress and warpage. Uneven adhesive thickness and adhesive defects also affect the resonance frequency of the resonator. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2475